Professional military education under martial law: personnel challenges, motivational mechanisms, and the effectiveness of the admission campaign - Loishyn, Anatolii (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The training of officer personnel within higher military education institutions constitutes an integral component of the strategic planning of the personnel potential of the Armed Forces of Ukraine. At the same time, the implementation of the state recruitment directive faces challenges, including competition between higher military educational institutions and both domestic and foreign civilian educational establishments for applicants, which are further exacerbated by martial law and the outflow of young people abroad. The purpose of this study is to identify ways to improve the system of selecting and training officer personnel in the Armed Forces of Ukraine through an analysis of educational, social, and communication factors.M e t h o d s . To achieve the research objective, the following methods were employed: analysis and synthesis – to define the research problem and purpose; content analysis – to examine sources related to the topic; concretization – to determine measures aimed at improving the organization of work with applicants in higher military education institutions; forecasting – to evaluate the expected outcomes of changes in the functionality and coordination among key actors involved in the admission campaign; generalization and systematization – to process the factors influencing the effectiveness of the admission campaign within the higher military education system.R e s u l t s . The current state of career orientation activities with applicants was characterized. Proposals for updating regulatory documents concerning military-professional guidance of youth were developed. Recommendations were substantiated regarding the content and coordinated functioning of individual structural units within higher military education institutions to enhance the effectiveness of the admission campaign. Both quantitative and qualitative indicators were identified.C o n c l u s i o n s . Officer personnel training is carried out through professional military education courses (L-1A + L-1B) or through studies within higher military education institutions. There are objective factors that influence applicants′ choice in favor of civilian – particularly foreign – educational institutions. The effectiveness of the admission campaign will depend, among other factors, on the adjustment of the functional responsibilities and authorities of recruitment and communication units, as well as coherence of their efforts. The results of the admission campaign should be evaluated based on clearly defined quantitative and qualitative performance indicators.
Keywords: higher military education institution, admission campaign, motivation, recruiting, communications, performance indicators